Hubungan Pertumbuhan Ekonomi dengan Inflasi di 90 Kabupaten-Kota Indonesia - Arifin, Samsul; Siregar, Hermanto; Anggraeni, Lukytawati; Purnamadewi, Yeti Lis (UI Scholars Hub, 2026)
This study aims to explain the relationship between economic growth and inflation in 90 Indonesian cities during the period 2018–2022 using the GMM estimator with Windmeijer - Sigmund robust standard errors. The author’s findings reveal that the two-way relationship between the two is that economic growth has a significant positif effect on inflation, while inflation has a negatif but insignificant effect. Through the results of this study, policymakers and stakeholders can consider priority objectives, namely achieving economic growth targets compared to inflation problems during the COVID-19 crisis and economic development during the future economic recovery.